Priming the Pump into Action: Institutions of Culture, Amateur Drama and Paradigm Shift in 1950s Ireland - Kennedy, Ian G (Irish Journal of Arts Management and Cultural Policy, 2021)
Focusing on case studies that deal with An Tóstal and the North Cork Drama Festival, this paper argues that amateur drama festivals, supported by the Arts Council/An Chomhairle Ealaíon, dynamically contributed to the paradigm shift that took place within post-war Irish society. The seventieth anniversary of the passing of the first Arts Act (1951) and the establishment of the Arts Council/An Chomhairle Ealaíon provides an opportunity to reflect on the impact of amateur drama festivals on 1950s Irish society. This research considers the commissioning of the Report on the Arts in Ireland (1948), the passing of the first Arts Act (1951), the establishment of the Arts Council/An Chomhairle Ealaíon (1952) and the initiation of An Tóstal (1953), as a series of fundamental cultural responses on the part of the government to the reality of a post-war changing society. Consequently, the research on which this paper is based argues that the Arts Council/An Chomhairle Ealaíon support for local communities that fostered cultural appreciation was an essential element to the state’s response to this deteriorating economic situation. Focusing on case studies that deal with An Tóstal and the North Cork Drama Festival, this paper argues that amateur drama festivals, supported by the Arts Council/An Chomhairle Ealaíon, dynamically contributed to the paradigm shift that took place within post-war Irish society. Despite a perception that Irish culture was in decline a plethora of literary output, coupled with evidence from the Arts Council/An Chomhairle Ealaíon / An Chomhairle Ealaíon archive, demonstrates that these festival communities looked to culture as a means of creatively addressing that which ‘could not be spoken of in official Ireland’ (Garvin and Fanning, 2014, p. 186).